Blended Learning in Teaching Literary Appreciation - Erna Dwinata (STKIP PGRI Tulungagung, 2020)
Blended learning is a blend of two learning models, namely face-to-face learning and online learning / e-learning. The purpose of blended learning is to stimulate and foster students learning motivation. This article discusses blended learning studies that are applied in appreciation literary classes. There are 3 learning models focused in this study. The first is Persenolized online learning, small group discussions and project online presentations. The 7th semester students become research subjects. They are 18 students. from the results of the 3 methods applied during the 5 months of learning, it is obtained that the combination of the three models is very suitable to be used as a method in teaching literary appreciation. It can be concluded that the instructional model is appropriately determined by the suitability of educational model, technique and method of learning, and also facilities and infrastructure readines.